Why Donald Trump Should Be a Fervent Advocate of Using Ranked-Choice Voting in 2024. Issue 1 (22nd January 2022) - Cervas, Jonathan; Grofman, Bernard
ABSTRACT: This article builds on work by Devine and Kopko (2021) and Lacy and Burden (1999) who estimated a probit model of candidate choice from nationally representative survey data to determine the second choice of third-party voters. Using this model on 2020 election data, we show that the Libertarian candidate Jo Jorgenson probably cost Donald Trump victory in at least two states: Arizona and Georgia. Additionally, the popular-vote margin enjoyed by Joe Biden could have been between 260, 000 and 525, 000 fewer votes, using conservative estimates. The motivation for this article is to provide contrary evidence for two main misconceptions. First, that third-party candidates are "spoiling" elections for the Democrats. Our evidence clearly shows that third parties have the potential to hurt either of the two main parties; however, in 2020, it was Donald Trump who was hurt the most, although not consequentially. Second, some reformers believe that ranked-choice voting benefits the Democrats; again, we show that—all else being equal—in the 2020 presidential election, it was the Republicans who would have benefited by the change in rules because the majority of third-party votes went to the Libertarian candidate, whose voters prefer Republicans over Democrats 60% to 32%.